Analysis of Competencies for Comprehensive Security Management in Local Communities in Slovenia - Lobnikar, Branko (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The purpose of the paper is to develop a set of competencies for comprehensive security management in local communities and to justify the need for a clearly defined, professionalised role of the municipal/urban security manager, who coordinates the operations of plural institutions of police activity in the local environment. The main findings of the pilot study show that the key to the success of the municipal security manager is inter-institutional coordination, good knowledge of the legal and institutional framework, and the ability to manage crises and communicate effectively. Strategic planning of preventive measures and understanding of the local context, as well as ethical and privacy aspects, also play an important role. Areas that require additional strengthening are highlighted as cybersecurity, the systematic use of performance indicators, the principles of creating a safe space, and project and financial management. The study confirmed previous findings on the importance of the “core” competencies of the municipal security manager, and also emphasised the need to upgrade them with project-process and analytical-data competencies.